Association between thyroid autoimmunity and gestational diabetes mellitus in euthyroid women. Issue 2 (21st March 2022) - Sitoris, Georgiana; Veltri, Flora; Ichiche, Malika; Kleynen, Pierre; Praet, Jean-Philippe; Rozenberg, Serge; Poppe, Kris G
Abstract : Objective: Pregnant women with autoimmune (subclinical) hypothyroidism have an increased risk of developing gestational diabetes mellitus (GDM). However, this association remains controversial in euthyroid women with thyroid autoimmunity (TAI). Therefore, the aim of the study was to determine the association between TAI and GDM in euthyroid women in a logistic regression analysis with adjustments for baseline/demographic parameters. Methods: Cross-sectional study in 1447 euthyroid women who performed their entire clinical/biological workup and oral glucose tolerance test (OGTT) in our center. At median 13 (11–17) weeks of gestation, thyroid-stimulating hormone, free T4, and thyroid peroxidase antibodies (TPOAb) were measured, baseline characteristics were recorded, and an OGTT was performed between 24 and 28 weeks of pregnancy. Exclusion criteria were pre-pregnancy diabetes, assisted pregnancies, and women with (treated) thyroid dysfunction before or after screening. The diagnosis of GDM was based on 2013 World Health Organization criteria, and TAI was defined as TPOAb levels ≥60 kIU/L. Results: Two hundred eighty women were diagnosed with GDM (19.4%), 26.1% in women with TAI, and 18.9% in women without TAI ( P = 0.096). In the logistic regression analysis, TAI was associated with GDM in women older than 30 years (adjusted odds ratio 1.68 (95% CI, 1.01–2.78); P = 0.048). Maternal age >30 years, pre-pregnancy BMI ≥30 kg/m 2, and other than Caucasian background were also associated with GDM; aOR 1.93 (95% CI, 1.46–2.56); P < 0.001, 2.03 (95% CI, 1.46–2.81); P < 0.001 and 1.46 (95% CI, 1.03–2.06); P = 0.034, respectively. Conclusions: In older pregnant women, the presence of TAI in euthyroid women was associated with GDM. In line with the literature data, (higher) age and BMI were strongly associated with GDM. Future investigations should focus on treatments that might prevent the development of GDM in euthyroid women with TAI.